PENGEMBANGAN MODUL PROBLEM BASED LEARNINGUNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH DAN HASIL BELAJAR BIOLOGI SMA - Eka Vasia Anggis; Istamar Syamsuri; Herawati Susilo (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The objective of this research as follow: 1) developing and validating Human Excretion System Module Based Constructivism With Problem Based Learning (PBL) by module expert, and tested personally, before the actual tested to the SMA Laboratorium  UM in the 11th grade; 2) knowing the effectiveness of Human Excretion System Module Based Constructivism With PBL development product that been tested in the actual condition to improve problem solving skill and student learning result of Biology in SMA Laboratorium UM at 11th grade. This research method is research and development with the steps that been adjusted with researcher needs as follow: 1) Define step; 2) Design step 3) Develop step.Location of research is in the senior high school laboratorium Malang;The research result shows that content validation, obtained the percentage average of module feasibility from lecturer of learning material expert lecturer of material expert biology, and teacher in the 11th grade of Natural Science-3 have feasibility. In the personal test, student module has feasibility. Based the actual test, it is obtained the percentage of Lesson Study implemented which increases from the before meeting. Date of PBL implemented has increased 6%. From problem solving skill date, psychomotor learning resultaffective learning result have increased 4% and 3%. From cognitive learning result has the passing level 91%. Keywords: module, Problem Based Learning, problem solving skill, Biology learning result